L’Arbre des rues de Mexico : une ressource au-delà de son exploitabilité - Nora Itri (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Our relationship to nature has been dominated in western thought by an idea of human superiority, and regulated by market mechanisms throughout the world. Over time, this has generated a form of smoothing in urban environments, in which the tree loses its quality as a living being and becomes an "urban object". In the streets of Mexico City, however, the tree defies this logic and stands out as a revelation of the continuity between the city and the natural environment. In this context, the tree acquires the status of "mediator", between a deeply artificialized environment created by humankind and the underlying biological territory that makes up the Mexico City Valley. Analyzing this particularity in the physical and historical constitution of the Mexican megalopolis allows us to renew the meaning that is conventionally attributed to the notion of resource. Left to its natural existence, Mexico City’s ‘‘tree of the street’’ supplants this global condition of exploitability to reveal the richness of its interactions with the environment, which are both natural and cultural. From the original design of Mexico City by the altepetl, the Aztec city-state, to the contemporary megalopolis, the ‘‘tree of the street’’ translates the persistent continuity of the natural environment through the city's soil. It is the expression of a form of cultural and conceptual interbreeding, and bears witness to the hybridity that has characterized Mexico City from its foundations. This singularity makes it possible to renew the ways in which we consider relationships between city and nature, between the artificial and the living, and between exploitation and interaction.